Precision Therapy for a Chinese Family With Maturity-Onset Diabetes of the Young - Li, Juyi; Shu, Meng; Wang, Xiufang; Deng, Aiping; Wen, Chong; Wang, Juanjuan; Jin, Si; Zhang, Hongmei (Frontiers in Endocrinology, 2021)
Objective To determine the pathogenic gene and explore the clinical characteristics of maturity-onset diabetes of the young type 2 (MODY2) pedigree caused by a mutation in the glucokinase (GCK) gene. Methods Using whole-exome sequencing (WES), the pathogenic gene was detected in the proband—a 20-year-old young man who was accidentally found with hyperglycemia, no ketosis tendency, and a family history of diabetes. The family members of the proband were examined. In addition, relevant clinical data were obtained and genomic DNA from peripheral blood was obtained. Pathologic variants of the candidate were verified by Sanger sequencing technology, and cosegregation tests were conducted among other family members and non-related healthy controls. After adjusting the treatment plan based on the results of genetic testing, changes in biochemical parameters, such as blood glucose levels and HAblc levels were determined. Results In the GCK gene (NM_000162) in exon 9, a heterozygous missense mutation c.1160C > T (p.Ala387Val) was found in the proband, his father, uncle, and grandmother. Thus mutation, which was found to co-segregate with diabetes, was the first discovery of such a mutation in the Asian population. After stopping hypoglycemic drug treatment, good glycemic control was achieved with diet and exercise therapy. Conclusion GCK gene mutation c.1160C > T (p.Ala387Val) is the pathogenic gene in the GCK-MODY pedigree. Formulating an optimized and personalized treatment strategy can reduce unnecessary excessive medical treatment and adverse drug reactions, and maintain a good HbA1c compliance rate